Left main bronchus compression by massive pericardial effusion: A rare cause of respiratory distress in an infant: A case report - K. C. Sudeep; Suresh Kumar Angurana; Harshita Nori; Sanjeev Hanumantacharya Naganur; Anmol Bhatia (Wolters Kluwer Medknow Publications, 2024)
Tracheobronchial compression due to cardiovascular disease is a rare cause of respiratory distress in children, and common causes include vascular slings and rings, abnormal origin of major vessels, and left atrial enlargement. Intrathoracic airway compression due to pericardial effusion is a rare cause of respiratory distress in children. Here, we present a 6-month-old male child who presented with respiratory distress due to extraluminal compression of the left main bronchus by large pericardial effusion leading to left lung collapse, which improved after pericardiocentesis.